Engaging High School Students with Ruangguru: An Innovative Online Learning Approach: Meningkatkan Keterlibatan Belajar Siswa SMA dengan Aplikasi Ruangguru: Pendekatan Inovatif dalam Pembelajaran Online - Pratiwi, Eka; Rochmaniah, Ainur (Indonesian Journal of Education Methods Development, 2023)
This qualitative research investigates the reception of high school students towards the Ruangguru application, a popular online medium of study. The study utilizes in-depth interviews, observations, and literature review to explore students' experiences with the application and its features. Purposive sampling was employed to select informants. The findings reveal that two informants dominate the hegemonic position, indicating their belief in the suitability of the application. Additionally, eight informants highlight the innovative nature of animated delivery in enhancing learning engagement. This research contributes to the understanding of student perspectives on using Ruangguru and has implications for improving online learning experiences globally. Highlights: The study explores the reception of high school students towards the Ruangguru application as an online medium of study, providing insights into its effectiveness and suitability. The research method involves qualitative data collection through in-depth interviews, observations, and literature review, allowing for a comprehensive understanding of students' experiences with the application. The findings reveal the dominant position of two informants who consider the Ruangguru application suitable, while eight informants emphasize the innovative nature of animated content delivery in enhancing student engagement and overcoming fatigue. Keywords: Ruangguru application, high school students, online medium of study, reception, qualitative research